Diversity of Entomopathogenic Fungi in Rice Field Bunds: Role of Soil Properties and Weed Vegetation for Integrated Pest Management - Afandhi, Aminudin; Pamungkas, Bayu Aji; Rachmawati, Rina; Syib’li, Muhammad Akhid; Karina, Anisya Putri; Fernando, Ito; Puspitarini, Retno Dyah; Setiawan, Yogo (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Rice field bunds function as a reservoir of biodiversity, one of which is entomopathogenic fungi (EPF), which plays a role in controlling insect populations and increasing plant resistance. This study aimed to explore the interaction between organic matter content, soil pH, and EPF diversity in rice fields from Mulyoagung Subdistrict, Malang Regency. EPF was isolated using the insect bait method, followed by pathogenicity testing on Tenebrio molitor larvae. The Shannon-Wiener index (H'), evenness (E), and dominance (C) were used to assess the diversity of EPF on rice field bunds. Spearman correlation analysis was conducted to test the relationship between organic matter content, soil pH, and EPF diversity. Based on the results of the study, three genera of EPF were found in the rice fields, namely Beauveria, Fusarium, and Metarhizium. The presence of EPF is influenced by understory plants and the amount of organic matter in the soil. Therefore, preserving rice field bunds is very important to maintain the EPF population.